Trust as a Mediating Variable of the Influence of Social Media Marketing and Content Quality on Purchase Decision (A Study on TikTok Users in Malang City) - Ita Prihatining Wilujeng; Ely Siswanto; Diki Egie Nugraha (Jurnal Ekonomi Balance, 2025)
This study analyzes the influence of social media marketing and content quality on purchase decisions, with trust positioned as a mediating variable, among TikTok users in Malang City, Indonesia. The rapid growth of TikTok as a short-video–based social media platform has reshaped digital marketing strategies and consumer behavior, making it important to understand how marketing activities and content characteristics affect purchasing decisions. This research employs a quantitative approach using a survey method. Data were collected from 180 active TikTok users who have made purchases influenced by marketing content on the platform. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that social media marketing has a significant positive effect on purchase decisions and trust. Similarly, content quality significantly influences both purchase decisions and consumer trust. However, trust does not have a significant direct effect on purchase decisions and does not mediate the relationship between social media marketing, content quality, and purchase decisions. These results indicate that TikTok users’ purchasing behavior is primarily driven by direct marketing exposure and the quality of content rather than by trust-based considerations. This study contributes to the digital marketing literature by providing empirical evidence that challenges the mediating role of trust in short-video social media platforms. Practically, the findings offer valuable insights for marketers and business practitioners to focus on developing effective social media marketing strategies and high-quality content to enhance consumer purchase decisions in competitive digital environments.